Therapeutic effects of Artocarpus communis J.R.Forst. & G.Forst. seeds on letrozole-induced polycystic ovary syndrome wistar rats - Akingbolabo Daniel Ogunlakin; Oluwafemi Adeleke Ojo; Damilare Iyinkristi Ayokunle; Peluola Olujide Ayeni; Dare Ezekiel Babatunde; Idayat Adeola Akinwumi; Owoola Azeezat Ambali; Oyindamola Esther Awosola; Mubo Adeola Sonibare (Elsevier, 2024)
Background: Herbal extracts are an effective treatment for polycystic ovarian syndrome (PCOS) and have been shown to improve insulin resistance, hyperandrogenism, sex hormones, ovulation, and PCOS symptoms. Artocarpus communis seed's potential effects on polycystic ovary syndrome (PCOS) have not been studied. Purpose: This research aims to investigate the beneficial effects of Artocarpus communis seeds on PCOS induced by letrozole in Wistar rats. Methods: To induce PCOS, female Wistar rats weighing between 160 g to 250 g were administered letrozole (1 mg/kg) for 21 days. Subsequently, for 12 days, the rats were given the Artocarpus communis seed methanol extract, and its hexane, DCM, ethyl acetate and aqueous fractions (100 mg/kg body weight) and Clomiphene citrate (1 mg/kg body weight), a standard medication. Luteinizing hormone (LH), follicle-stimulating hormone (FSH), and estradiol levels were assessed using ELISA, and the expression of P53, insulin receptor substrate (IRS), type 2 17-HSD (17-HSD), fat mass and obesity-associated (FTO), and 11a-hydroxylase/17,20-desmolase (CYP11a) genes were investigated. The data were analyzed using one-way ANOVA, and a significance threshold of p < 0.05 was set for Dunnett's Multiple Comparison Test. Results: Administration of the methanol extract of Artocarpus communis seed and its Hexane fraction led to a decrease in LH level and an increase in FSH and estradiol levels in the PCOS-induced animals. Furthermore, methanol extract, DCM, and ethyl acetate fraction normalize the expression of P53, insulin receptor substrate (IRS), type 2 17-HSD (17-HSD), fat mass and obesity-associated (FTO), and 11a-hydroxylase/17,20-desmolase (CYP11a) genes in PCOS rats cervix. Conclusion: Artocarpus communis seed exhibited ameliorative effects on polycystic ovary conditions in Wistar rats, suggesting its potential use in the management of PCOS.